MENINGKATKAN MOTIVASI BERWIRAUSAHA MAHASISWA DILINGKUNGAN KAMPUS STISIP WIDYAPURI MANDIRI MELALUI PROGRAM KEWIRAUSAHAAN - Eko Setio Budi (STISIP Widyapuri Mandiri, 2023)
The government through the ministry, especially the ministry of education and culture, continues to increase the number of entrepreneurs through entrepreneurship competition programs. One of these entrepreneurship competition programs includes the Indonesian Student Entrepreneurship Activity Program (PKBMI) in 2021 and the Student Entrepreneurship Implementation Program (P2MW) in 2022 organized by the Ministry of Research and Technology Education and Culture through the Directorate General of Higher Education and the Directorate of Belmawa. It is hoped that the launch of these entrepreneurship programs can further spur and trigger entrepreneurial motivation, especially among students at public and private universities. Stisip Widyapuri Mandiri, one of the private universities in Sukabumi Regency, welcomed and enthusiastically participated by implementing the entrepreneurship program launched by the government through socialization and direct selection of participating students. It is hoped that the participation of the institution and the participation of students in the entrepreneurship program competition can further increase the motivation for entrepreneurship.